Satuan Lingual Yang Mengandung Pronomina Persona Pertama Dan Kedua Pada Teks Terjemahan Hadis Pada Buku Sahih Buchori Muslim - ILHAM PRASTIKA, OKTAVIA, Prof. Dr. Abdul Ngalim, M.M, M.Hum, Prof. Dr. Markhamah, M.Hum (2015)
This research has three objectives. First, describing the form category and define the linguistics hierarchy in a lingual unit which is contain first and second persona pronoun on the hadith text translation. Second, describing the function which is residing a lingual unit contains the first and the second persona pronoun in the hadith translation text. Third, determine the role which is reside in a lingual unit contain the first and the second persona pronoun in the hadith text translation. The sort of this research is qualitative descriptive. The sources of the data are documents or archives about information which is written in the hadith text translation. The method of collecting data in this research is using the method of scrutinize and record. At first the researcher scrutinize the hadith text translation, then identify the data which is contain the first and the second persona pronoun, and then classify and record by identifying the hadith text translation which is contain the first and the second persona pronoun, and the last is analyzing it. The data analysis method is using parable and apportion method. Apportion method is used to describe lingual hierarchy which is contain PP1 and PP2 in hadith text translation, and the parable method is used to analyze the function, category, and the role in hadith text translation. There are three results in this thesis, first is linguistics hierarchy and category form in a lingual unit of PP1 and PP2 in the hadith text translation that is word and phrase. Lingual unit which contain word cover the word of noun. Lingual unit which contain phrase cover Noun Phrase, Prepotional Phrase, Enclitic, Verb Phrase, Attributive Phrase, and Adjective Phrase. Second, the function that fulfilled by a unit of lingual which is contains of PP1 and PP2 are Subject, Predicate, Object, and Complement. Third, the function that fulfilled by a unit of lingual which is contains PP1 and PP2 in the hadith translation text are a role of subject, a role of experience, a role of direction/destination, a role of accusative, a role of deed, a role of the way, a role of time, a role of participation, and a role comparison.